Natural Communication Abilities Among Children with Congenital Deafblindness in Multi-Linguistic Communities of Zambia - Brighton Kumatongo; Douglas Gawani Phiri (Journal of General Education and Humanities, 2022)
Children with Deafblindness in Zambian communities face communication challenges. Communication forms the basis for human interaction, exchanging ideas and feelings, and facilitating inclusiveness in society. This study, anchored on the theory of dialogism as the theoretical framework, sought to assess the natural communication abilities of children with congenital Deafblindness and further explore measures taken by caregivers/parents to enhance the communication abilities of the children. A qualitative case study was used as the research design. Snowball sampling technique was used to sample three (3) children with congenital Deafblindness aged three (3), eleven (11), and twelve (12) and three (3) parents and one (1) relative who participated in the study, making the total number of (7) seven participants. The participants were from Lusaka, Copperbelt, and Northwestern provinces of Zambia. The findings were that children with congenital Deafblindness could use natural signs to communicate their feelings of happiness, frustration, or discomfort, detect sounds, express mistreatment, and use imitations, tapping, and pointing signs. The study concluded that although children with congenital Deafblindness can communicate, parents 1 and 2 naturally and relative o In contrast, parent 3 was able to communicate with her child with congenital Deafblindness through the use of Hand overhand communication, the object of reference, body contact and hand tactile techniques. The study recommended the need to teach communication techniques to parents and caregivers of children with Deafblindness in order to improve the communication skills of children with Deafblindness.